Book Reviews Vol12 no2 - Laura Steckley; Ian Milligan; Robyn Kemp; Kiaras Gharabaghi; Dawn Simpson; Evelyn Vrouwenfelder (Scottish Journal of Residential Child Care)
There has been a bumper crop of books dedicated to social pedagogy this year – a fortuitous situation for providing a series of relevant reviews for this special issue of the Journal. This offers a nice opportunity to compare, in this case, three newly-published books on social pedagogy. Each of our reviewers gives a nice sense of the tone and slant of their books, giving an indication of some of the differences between them. I hope this will be helpful in deciding about further reading. Another of our reviews in this issue is on a book dedicated to storytelling and while it does not explicitly address social pedagogy, the reviewer clearly and adeptly provides strong connections between the book's content and the practice and philosophy of social pedagogy. Finally, it was no mean feat to find a seminal text or author from the social pedagogic tradition written in English, but we have managed to do so and thus provide a review of a book originally written by Janusz Korczak. Thanks to Ian Milligan, Robyn Kemp, Kiaras Gharabaghi, Dawn Simpson and Evelyn Vrouwenfelder for their generous contributions to our book review section.